Pět přátel Franze Kafky aneb Co skrývá povídka „Společenství“ // Franz Kafka!s five friends or the hidden message of the short story "Fellowship" - Jaroslav Březina (Svět Literatury, 2018)
The article focuses on one of Kafka’s short parables written in September 1920 and published for the first time in 1936. The text tells — from the first person plural perspective — about a group of five friends, and a sixth person who vainly seeks entrance into their brotherhood. The article discusses Kafka’s “analysis” of the inclusionary and exclusionary dynamics of this group formation, as well as the question about the fiction of this community. Confronted with contemporary events and episodes of Kafka’s life, there will also be a presumption of Kafka’s reflection of racial and national tensions with its anti-Semitic and anti-German incidents and demonstrations that disrupted life in Prague in 1920.